Marker-assisted selection in the development of advanced apple-tree forms and donors combining scab resistance with increased fruit storability - I. I. Suprun; E. A. Egorov; A. I. Nasonov; E. V. Lobodina; S. V. Tokmakov; I. V. Stepanov (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Cultivation of scab-resistant apple cultivars with better fruit storability increases the economic efficiency and environmental friendliness of horticulture. Hence, the development of such cultivars is an important task in modern apple-tree breeding.Materials and methods. A set of 646 hybrid plants obtained in six cross combinations (Renet Simirenko/Modi, Renet Simirenko/Smeralda, Renet Simirenko/Renoir, Renet Simirenko/Fujion, Renoir/Granny Smith, and Modi/Granny Smith) was studied. Their scab resistance was assessed under natural infection pressure for two years using a quantitative scale. The Rvi6 gene was identified using the PCR analysis with the primer pair VfC1+VfC. The Md-ACS1 gene alleles were detected with a known SCAR DNA marker. The chi-square test was applied for statistical confirmation of the data.Results. Based on the DNA marker analysis, 328 plants carrying the dominant allele of the Rvi6 gene were identified. The results of the phenotypic resistance assessment confirmed the correspondence of the resistant phenotype / dominant allele of the gene for most plants. Molecular genetics analysis of the Md-ACS1 gene disclosed its allelic combinations. A total of 190, 322, and 126 plants carrying allelic variants of Md-ACS1-2/2, Md-ACS1-1/2, and Md-ACS1-1/1, respectively, were identified. Among the plants with the dominant allele of the scab resistance Rvi6 gene, 92 plant forms were identified with Md-ACS1-2/2, and 143 heterozygous ones (Md-ACS1-1/2), also valuable for breeders.Conclusion. A wide range of apple breeding forms carrying valuable alleles of the Rvi6 and Md-ACS1 genes were selected. Hybrid forms with target alleles of both genes responsible for important agronomic traits would contribute to the intensification of breeding efforts aimed at producing scab-resistant apple cultivars with increased fruit storability. They can also be used for breeding purposes as complex donors.